1979
DOI: 10.1088/0029-5515/19/8/004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drift modes on currentfree plasma transport processes in a stellarator

Abstract: The authors measure the losses of charged particles and heat via the electrons in the toroidal ℓ = 3 Saturn stellarator with large shear (θmax ≲ 0.25). From an analysis of the relationships derived they conclude that the pseudoclassical nature of the energy losses observed is due to the presence of drift modes in the plasma. The particle losses for shear θ < 0.05 are determined by the turbulence of the plasma, whereas at θ > 0.05 the diffusion both in magnitude and functional dependence matches the neoclassica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Theoretical studies [1][2][3][4] have shown that the level of these oscillations and the plasma losses caused by them can be substantially reduced if the magnetic configuration has a sufficiently large shear or a magnetic well. The stabilizing role of both these factors has also been confirmed by numerous experiments in open [5][6][7][8] and closed [9][10][11][12][13][14][15]23] magnetic traps.…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…Theoretical studies [1][2][3][4] have shown that the level of these oscillations and the plasma losses caused by them can be substantially reduced if the magnetic configuration has a sufficiently large shear or a magnetic well. The stabilizing role of both these factors has also been confirmed by numerous experiments in open [5][6][7][8] and closed [9][10][11][12][13][14][15]23] magnetic traps.…”
Section: Introductionmentioning
confidence: 65%
“…It was shown earlier on this device [11] that with increasing shear there is a decrease in the level of lowfrequency fluctuations in some parts of the frequency spectrum, 2 kHz < f < 20 kHz. This result is confirmed by the data of Fig.…”
Section: Fig8 the Influence Of Shear On The Amplitude Of Oscillations...mentioning
confidence: 71%
See 3 more Smart Citations